2005
DOI: 10.1086/498164
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of an Adjuvanted Human Papillomavirus (HPV) Type 6 L2E7 Vaccine: Infection of External Anogenital Warts with Multiple HPV Types and Failure of Therapeutic Vaccination

Abstract: Infection with multiple HPV types, including high-risk types, is common in anogenital wart disease. Therapeutic vaccination failed to increase the efficacy of conventional therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 42 publications
5
64
0
2
Order By: Relevance
“…All AEs reported were transient, and most resolved within 1 to 4 days. The pattern of AEs observed has previously been reported with other vaccines containing AS02 A (14,16,37,(40)(41)(42). No clinically significant changes in laboratory test (biochemistry and hematology) values related to vaccination were observed.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…All AEs reported were transient, and most resolved within 1 to 4 days. The pattern of AEs observed has previously been reported with other vaccines containing AS02 A (14,16,37,(40)(41)(42). No clinically significant changes in laboratory test (biochemistry and hematology) values related to vaccination were observed.…”
Section: Discussionsupporting
confidence: 79%
“…In order to evaluate the magnitude of the cell-mediated immune response elicited by the Mtb72F/ AS02 A vaccines, PBMCs were restimulated in vitro and analyzed by ICS and flow cytometry. A high frequency of Mtb72F-specific CD4 ϩ T cells expressing two or more immune markers among the markers CD40L, IL-2, TNF-␣, and IFN-␥ was measured after 2 and 3 immunizations for 10 g Mtb72F/AS02 A (median frequencies, 0.19% and 0.23%, respectively) and 40 g Mtb72F/AS02 A (median frequencies, 0.28% and 0.15%, respectively) (Fig. 2).…”
Section: Study Populationmentioning
confidence: 98%
“…HPV vaccine has been proven efficacious in preventing the HPV infections of the cervix and anogenital tract (7). However, the role of HPV vaccine in preventing RRP is not clear yet and it is less likely to be of therapeutic value (8). In this case, after the boy underwent the surgical removal via electrocautery and the adjuvant treatments of acyclovir and IFN-α, the lesions were cured in a short time and had not recurred for one year, which indicated that the combination of multiple treatment modalities is one of the feasible treatment regimens.…”
Section: Discussionmentioning
confidence: 87%
“…Two trials were performed using the VLP of HPV6 (Zhang et al, 2000) or the fusion protein L2E7 fron HPV6 (Lacey et al, 1999;Thompson et al, 1999;Vandepapeliere et al, 2005) with a clearance of condyloma obtained in 75 and 20% of cases, respectively. In the absence of control group in these trials, it is too early to make conclusions about the efficacy of these vaccines.…”
Section: How To Cure Infection / Tumorigenesis? Therapeutic Vaccinesmentioning
confidence: 99%